2021
DOI: 10.21037/atm-21-6274
|View full text |Cite
|
Sign up to set email alerts
|

Voice parameters for difficult mask ventilation evaluation: an observational study

Abstract: Background: Mask ventilation (MV) is an essential component of airway management. Difficult mask ventilation (DMV) is a major cause for perioperative hypoxic brain injury; however, predicting DMV remains a challenge. This study aimed to determine the potential value of voice parameters as novel predictors of DMV in patients scheduled for general anesthesia. Methods: We included 1,160 adult patients scheduled for elective surgery under general anesthesia. The clinical variables usually reported as predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Research has shown that a difficult airway assessment model constructed by phonetic features (5 vowels and 5 formant frequencies) has value in predicting difficult laryngoscopy and difficult mask ventilation with an AUC of 0.761 and 0.74, respectively and the combination with Modified Mallampati test (MMT) can achieve an even better performance ( 123 , 124 ). In Chinese populations, acoustic features including formant frequencies (f1–f4) and bandwidths (bw1–bw4) were predictive of difficult laryngoscopy and difficult mask ventilation with an AUC of 0.709 and 0.779, respectively ( 125 , 126 ).…”
Section: New Technologies Currently Under Developmentmentioning
confidence: 99%
“…Research has shown that a difficult airway assessment model constructed by phonetic features (5 vowels and 5 formant frequencies) has value in predicting difficult laryngoscopy and difficult mask ventilation with an AUC of 0.761 and 0.74, respectively and the combination with Modified Mallampati test (MMT) can achieve an even better performance ( 123 , 124 ). In Chinese populations, acoustic features including formant frequencies (f1–f4) and bandwidths (bw1–bw4) were predictive of difficult laryngoscopy and difficult mask ventilation with an AUC of 0.709 and 0.779, respectively ( 125 , 126 ).…”
Section: New Technologies Currently Under Developmentmentioning
confidence: 99%
“…Among the Chinese population, phonetic characteristics incorporating formant frequencies (f1–f4) and bandwidths (bw1–bw4) effectively predicted difficult intubation and mask ventilation with an AUC of 0.709 and 0.779, respectively. [ 27 28 ] A step further would be to combine acoustic analysis with multi-lingual machine translation (MMT) techniques, which is thought to improve the model’s accuracy. [ 29 30 ]…”
Section: Ai In Difficult Airway Assessment and Managementmentioning
confidence: 99%